AKTIVITAS ANTIDIABETES SENYAWA FLAVONOID DAN ALKALOID JAMUR Pleurotus cystidiosus SEBAGAI INHIBITOR ENZIM PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR GAMMA (PPAR-γ) DAN GLYCOGEN PHOSPHORYLASE: STUDI INSILICO - Nuniek Ina Ratnaningtyas; Fajar Husen (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2026)
Pleurotus cystidiosus mushroom is a food mushroom with antidiabetic and antioxidant activities. However, utilizing this mushroom as a candidate for herbal medicine is still very rare. This study aims to evaluate the potential antidiabetic activity of flavonoid and alkaloid compounds contained in P. cystidiosus mushroom through an in silico approach as inhibitors ofPeroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Glycogen Phosphorylase (GP) enzymes. PPAR-γ and GP are essential therapeutic targets in the management of type 2 diabetes mellitus because they play a role in the regulation of glucose and lipid metabolism. In this study, active compounds were identified through a literature review, and then analyzed for molecular interactions using the molecular docking method against PPAR-γ and GP crystal structures obtained from the Protein Data Bank (PDB) database. The docking results show that some flavonoid and alkaloid compounds have strong binding affinity towards both enzyme targets, as indicated by low binding energy values and significant hydrogen interactions with active residues. The binding affinity values of flavonoids and alkaloids to PPAR-γ were -5.3 and -6.9 kcal/mol, while those to GP were -7.9 and -6.8 kcal/mol. This study indicates that bioactive compounds from P. cystidiosus can potentially be candidate inhibitors of PPAR-γ and GP, and can be further developed as antidiabetic agents. Further in vitro and in vivo studies are recommended to confirm these compounds' biological activity and safety.